2010
DOI: 10.1021/ma901693c
|View full text |Cite
|
Sign up to set email alerts
|

Composition-Dependent Morphological Transitions and Pathways in Switching of Fine Structure in Thin Films of Block Copolymer Supramolecular Assemblies

Abstract: The phase behavior of supramolecular assemblies (SMA) formed by polystyrene-blockpoly(4-vinylpyridine) (PS-b-P4VP) with 2-(4 0 -hydroxybenzeneazo)benzoic acid (HABA) was investigated with respect to the molar ratio (X) between HABA and 4VP monomer unit in bulk as well as in thin films coated on a silicon substrate. In bulk, the SMA showed bcc packed spherical or hexagonally packed cylindrical microdomains composed of P4VP(HABA) blocks in PS matrix depending on the composition which varied with the HABA weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 39 publications
3
81
0
Order By: Relevance
“…33−35 For supramolecular thin films, the effects of annealing solvents on the morphology of polystyrene-b-poly(4-vinylpyridine) (PS-b-P4VP) with 2-(4′-hydroxybenzeneazo) benzoic acid (HABA) molecules have been reported by Minko and co-workers. 22,36,37 They found that as films were annealed by chloroform, the P4VP(HABA) cylindrical microdomains were parallel to the surface, while annealed by 1,4-dioxane, the cylinders were perpendicular to the surface, which was attributed to the different selectivity of the solvents to each phase. The previous discussions of block copolymer-based supramolecules have been generally under the presumption that the small molecules are firmly grafted on the polymer chains.…”
Section: ■ Introductionmentioning
confidence: 99%
“…33−35 For supramolecular thin films, the effects of annealing solvents on the morphology of polystyrene-b-poly(4-vinylpyridine) (PS-b-P4VP) with 2-(4′-hydroxybenzeneazo) benzoic acid (HABA) molecules have been reported by Minko and co-workers. 22,36,37 They found that as films were annealed by chloroform, the P4VP(HABA) cylindrical microdomains were parallel to the surface, while annealed by 1,4-dioxane, the cylinders were perpendicular to the surface, which was attributed to the different selectivity of the solvents to each phase. The previous discussions of block copolymer-based supramolecules have been generally under the presumption that the small molecules are firmly grafted on the polymer chains.…”
Section: ■ Introductionmentioning
confidence: 99%
“…147 However, none of the BCP complexes they prepared involved azobenzene guests. On the other hand, Xu and co-workers, 148 Stamm and coworkers, [149][150][151] and, recently Gröschel and coworkers, 152 have used azobenzene-containing hydrogenbonded side chains in investigations involving thin-film nanopatterning, nanoparticle assembly, and templating with supramolecular BCPs, but they did not explore the potential photoresponsive properties of these complexes. Photoinduced control over the phase structure of BCP materials combined with supramolecularly bonded azobenzene molecules is a highly interesting phenomenon, which has only recently begun to be explored.…”
Section: Photocontrol Of Micro-and Nanostructures Through Supramolecumentioning
confidence: 99%
“…During the self-assembly process, increasing the reaction time can produce directional effects on the organic-organic interface, and affect space groups, pore orientations, and stress direction (Nandan et al, 2010). The two main models, cylindrical and spherical micelles were generated to minimize the surface free-energy of a system (Jin et al, 2011), and such micelles can associate, which corresponds to the liquid crystal mesophase.…”
Section: Thermal Analysismentioning
confidence: 99%